2023
DOI: 10.7717/peerj.14863
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-mediated m6A modification of has_circ_0007905 promotes age-related cataract progression through miR-6749-3p/EIF4EBP1

Abstract: Many cases of blindness are caused by age-related cataracts (ARCs). N6-methyladenosine (m6A)-modified circRNA widely participates in disease progression. However, the role of m6A modification of circRNA in ARC is unclear. We mined and elucidated the functions and mechanisms of key circRNAs with m6A modification involved in ARC progression. The GSE153722 dataset was used to mine m6A-mediated key circRNA. Loss-of-function assays and rescue assays were used to explore the effect and mechanism of circRNA on ARC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Specifically, among these 3,755 circRNAs, 3,742 exhibited hypermethylation while 13 showed hypomethylation ( Figure 1 ). Accumulating evidence has shown that aberrant m6A modification of circRNAs contribute to the development of various diseases, including hepatocellular carcinoma ( Chen et al, 2022 ), innate immune system inhibition ( Chen et al, 2019 ), osteosarcoma ( Liu et al, 2023 ) and age-related cataract progression ( Li et al, 2023 ). These suggest that the m6A-modification patterns of circRNA found in our study may play a significant role in the pathogenesis of middle ear cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, among these 3,755 circRNAs, 3,742 exhibited hypermethylation while 13 showed hypomethylation ( Figure 1 ). Accumulating evidence has shown that aberrant m6A modification of circRNAs contribute to the development of various diseases, including hepatocellular carcinoma ( Chen et al, 2022 ), innate immune system inhibition ( Chen et al, 2019 ), osteosarcoma ( Liu et al, 2023 ) and age-related cataract progression ( Li et al, 2023 ). These suggest that the m6A-modification patterns of circRNA found in our study may play a significant role in the pathogenesis of middle ear cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aberrant DNA methylation in imprinting control regions can also affect the expression of miRNAs associated with imprinting control regions [ 45 ]. Moreover, changes in transcription factors and m 6 A modifications may also play an important role in the regulation of miRNA expression [ 20 , 46 ]. Therefore, in this study, numerous altered miRNAs in the F2 and F3 generations may also be regulated by multiple mechanisms as described above.…”
Section: Discussionmentioning
confidence: 99%
“…C ataract is the first reversible blindness-causing eye disease worldwide; however, the underlying pathogenesis is yet inconclusive. Albeit age and some genetic factors 1,2 are the main causes of cataract formation. With the overall improvement in the social, economic, and medical development, the patients have put forward high requirements for the postoperative effect of cataract.…”
mentioning
confidence: 99%